HUBUNGAN ANTARA SELF REGULATED LEARNING DAN LOCUS OF CONTROL INTERNAL DENGAN KEMATANGAN VOKASIONAL SISWA SMK - Lativa Hartiningtyas; Purnomo Purnomo; Hakkun Elmunsyah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
This research was held on all students SMK TKJ (computer and network engineering) in Tulungagung district. The purpose of this research was to study the relationship between self regulated learning and internal locus of control as independent variables and vocational maturity as a dependent variables. The population of this research was the whole grade XI program study computer and network engineering in Tulungagung district which amounts to 337 students. The sampling techniques used in this research was the proportionate random sampling. The number of samples in this research was 182 students. This research used a quantitative approach with the kind of research was descriptive correlational. The reserach instruments used questionnaire about self regulated learning, internal locus of control, and vocational maturity with Likert scale which used 4 scales. Analysis data analysis this research used the correlation product moment to observe the relationship between independent variables with dependent variable partially and multiple regression analysis to figure out the relationship between independent variables with dependent variable simultaneously. Based on the data analysis can be observed that the coefficient of correlation between X1 with Y was 0,511 and coefficient of correlation between the variable X2 with Y was 0,576.Penelitian ini dilaksanakan pada SMK TKJ (Teknik Komputer dan Jaringan) se-Kabupaten Tulungagung. Tujuan dari penelitian ini adalah mengetahui hubungan antara self regulated learning dan locus of control internal sebagai variabel bebas (independent) dengan kematangan vokasional sebagai variabel terikat (dependent) pada siswa SMK. Populasi penelitian ini adalah seluruh siswa kelas XI Paket Keahlian TKJ di Kabupaten Tulungagung yang berjumlah 337 siswa. Teknik sampling yang digunakan dalam penelitian ini adalah proportionate random sampling. Jumlah sampel pada penelitian ini adalah 182 siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan penelitian deskriptif korelasional. Instrumen yang digunakan berupa angket self regulated learning, locus of control internal, dan kematangan vokasional yang menggunakan skala Likert dengan 4 skala. Analisis data pada penelitian ini menggunakan korelasi product moment untuk mengetahui hubungan antara variabel bebas dengan variabel terikat secara parsial dan analisis regresi ganda untuk mengetahui hubungan secara simultan antara variabel bebas dan variabel terikat. Berdasarkan analisis data dapat diketahui koefisien korelasi antara X1 dengan Y adalah sebesar 0,511 dan koefisien korelasi antara variabel X2 dengan Y adalah sebesar 0,576.